2019
DOI: 10.1039/c9ja00261h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sample temperature on the laser-induced breakdown spectroscopy of a molybdenum–tungsten alloy

Abstract: During laser ablation, the spectral emission intensity, plasma temperature and electron density increased significantly with increasing sample temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…However, the experimental results in Fig. 3 were inconsistent with the theoretical results, 52 which may be because (1) the rigidity of the gold decreases as the temperature of the sample increases, which causes a change in the interaction between the laser and the gold; (2) the difference between the high and low temperatures near the upper window of the sealed chamber causes an accelerated flow of air outside the chamber, which leads to a large loss of laser energy transmitted to the sample. Similarly, the air flow in the side windows also has an impact on the efficiency of spectrum acquisition; 56 (3) according to pV = nRT , the volume of air in the chamber remains constant but the temperature increases, resulting in an increase in pressure which enhances the binding of the plasma and the plasma shielding effect may also be enhanced.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the experimental results in Fig. 3 were inconsistent with the theoretical results, 52 which may be because (1) the rigidity of the gold decreases as the temperature of the sample increases, which causes a change in the interaction between the laser and the gold; (2) the difference between the high and low temperatures near the upper window of the sealed chamber causes an accelerated flow of air outside the chamber, which leads to a large loss of laser energy transmitted to the sample. Similarly, the air flow in the side windows also has an impact on the efficiency of spectrum acquisition; 56 (3) according to pV = nRT , the volume of air in the chamber remains constant but the temperature increases, resulting in an increase in pressure which enhances the binding of the plasma and the plasma shielding effect may also be enhanced.…”
Section: Resultsmentioning
confidence: 81%
“…Eschlböck-Fuchs et al 51 found that the LIBS signal intensity and the expansion process of the plasma are influenced by the matrix temperature. The experimental results showed that the LIBS signal intensity increased with increasing matrix temperature, and the expansion of the plasma volume was observed to be larger and brighter at 708 K than at 298 K. Hai et al 52 investigated the analytical capability of the LIBS technique on high-temperature nuclear materials from two perspectives: the effect of temperature on the surface morphology and depth profile of the ablation crater, respectively. They found that the metal surface reflectivity changes with the matrix temperature, leading to an increase in ablation which eventually increases the signal intensity.…”
Section: Introductionmentioning
confidence: 99%
“…As the plasma from the second pulse evolves close to hot target, it persists closer to LTE than the first plasma, yet the elongation of the its lifetime is weaker than for shorter IPDs. The enhancement of LIBS by reheating the target has already been considered by several authors [19,20].…”
Section: Comparison Of Density Results From Stark and Saha Equationmentioning
confidence: 95%
“…379.825 nm, 386.410 nm, and 390.295 nm are the prominent Mo( i ) lines. 39 Since the experiment is carried out in a partial vacuum, certain ambient gas lines can be seen in the spectrum. They are the Hα line at 656.285 nm (3d, 2 D 5/2 → 2p, 2 P 3/2 ), the N II line at 567.602 nm (2s 2 2p3p, 3 D 1 → 2s 2 2p3s, 3 P 0 ), and the Ar I line at 739.298 nm (3s 2 3p 5 ( 2 P 3/2 °)6s, 2 [3/2] 1 → 3s 2 3p 5 ( 2 P 3/2 °)4p, 2 [3/2] 1 ), all of which have a lower relative intensity than the constituent elemental lines of the sample.…”
Section: Resultsmentioning
confidence: 99%